B Cells and Antibodies Are Required for Resistance to the Parasitic Gastrointestinal Nematode Trichuris muris - Blackwell, Nathan M. (American Society for Microbiology, 2001)
Previous studies using cell transfers and antibody receptor knockout mice have shown that B cells and antibodies are not essential components of the expulsion mechanism in Trichuris muris infections. Serum transfer experiments have given mixed results regarding the importance of antibodies in this infection model, and the role of B cells in initiating or maintaining T-cell responses has not been addressed. We used B-cell-deficient μMT mice to determine if B cells play a role in anti-T. muris immune responses. In contrast to wild-type C57BL/6 mice, μMT mice were susceptible to infection. Antigen-restimulated mesenteric lymph node cells from infected μMT mice produced only naive levels of Th2-associated cytokines but had increased levels of gamma interferon. However, these mice appeared capable of mounting a Th2-dependent mucosal mastocytosis, though this was significantly delayed compared to that seen in wild-type mice. Resistance to T. muris was restored following reconstitution with naive C57BL/6 splenic B cells, as was in vitro Th2 cytokine production in response to parasite antigen. Treatment of μMT mice with anti-interleukin-12 monoclonal antibody during the first 2 weeks of infection also restored immunity, suggesting that μMT mice can be manipulated to expel worms at the time of T-cell priming. Additionally, treatment of μMT mice with parasite-specific immunoglobulin G1 purified from the serum of resistant NIH mice prevented worm establishment, suggesting an important role for antibodies. Our results as a whole describe the first detailed report of a critical role for B cells in resistance to an intestinal nematode.